Prevention of MANET from Co-Operative Black Hole Attacks (International Journal of Engineering and Computer Science, 2016)
A mobile ad hoc network (MANET) is an infrastructureless wireless    network and consists of mobile nodes. Secure communications among the mobile nodes are achieved by consequential challenges. These challenges are overcome by building the multiple security solutions that protect and enhance the network performance. One of the principal routing protocols used in Ad hoc networks is AODV protocol. The security of the AODV protocol is compromised by a particular     type     of       attack       called ‘Black Hole’ attack. Black hole attack is one of the severe attacks that come from misbehavior of the node. The misbehaving node acts as selfish or malicious. Malicious node is also called black hole. The black hole intercepts the packet and confidentiality of the message is disclosed. Our approach to combat the Black hole attack is to make use of a ‘Fidelity Table’. Fidelity level that acts as a measure of reliability of the node. And by the use of  Fidelity Table blackhole was detected and eliminated. The simulation was carried using NS-2 and the performance of the network is analyzed after removal of black hole attack